2023
DOI: 10.1039/d3tb00288h
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulin cargo loading: progress and potential

Abstract: Encapsulins are a recently discovered class of prokaryotic self-assembling icosahedral protein nanocompartments measuring between 24 and 42 nm in diameter, capable of selectively encapsulating dedicated cargo proteins in vivo. They...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 87 publications
1
10
0
Order By: Relevance
“…The disordered N-terminal domains have recently been proposed to function as cargo loading domains (CLD) in Family 2B encapsulin systems 22 . Similar N-terminal CLDs are found in Family 2A cysteine desulfurase cargo proteins and have already been confirmed as essential for cargo encapsulation 22,23,39,43 .…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The disordered N-terminal domains have recently been proposed to function as cargo loading domains (CLD) in Family 2B encapsulin systems 22 . Similar N-terminal CLDs are found in Family 2A cysteine desulfurase cargo proteins and have already been confirmed as essential for cargo encapsulation 22,23,39,43 .…”
Section: Resultssupporting
confidence: 67%
“…The CLDs of Family 2 encapsulins are extended and flexible domains rich in proline, glycine, and alanine 22,23,39,43 . Inspection of Sg 2-MIBS AlphaFold models suggests two CLD stretches with helical propensity which we used as markers to subdivide the Sg 2-MIBS CLD into five regions – CLD_A to CLD_E – for mutational and cargo-loading analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Encapsulins consist of self-assembling protein shells sequestering dedicated cargo enzymes and are among the most widespread protein compartments in prokaryotes ( 21 , 23 , 24 ). Cargo encapsulation is mediated by targeting sequences present at the N or C terminus of all cargo proteins ( 21 , 22 , 25 , 26 ). Encapsulin shells have icosahedral (I) symmetry with triangulation numbers of T = 1 (60 subunits, 24 nm), T = 3 (180 subunits, 32 nm), or T = 4 (240 subunits, 42 nm), and an evolutionary connection with viral capsids has been proposed ( 21 , 22 , 27 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we identified a putative single domain rhodanese (Ab-RLD) associated with an encapsulin nanocompartment operon found in Acinetobacter baumannii 14 . Encapsulin nanocompartments are self-assembling compartmentalization systems widespread in prokaryotes where cargo enzymes are specifically encapsulated inside 18 to 42 nm icosahedral protein shells 15,1618 . Encapsulins have been shown to be involved in iron storage 1921 , peroxide detoxification 22,23 , and sulfur metabolism 24 .…”
Section: Introductionmentioning
confidence: 99%